Propagation measurement, drain, radio wave, electromagnetic, wireless communications. - Lim, Soo Yong *; Liew, Yi Hong *; Seng, Kah Phooi * (2012)
Propagation measurement results were reported in a style of open-trench drain that is common in several Asian countries in [1]. In particular, measurement results at three frequencies, namely 900 MHz, 2.4 GHz, and 5.8 GHz were reported in three scenarios, whose findings are beneficial in designing wireless communication systems in environments where such drains are present. In this work, further investigation has been made on the contents inside an open-trench drain. This investigation is expected to contribute to a practically important propagation problem because in reality, the open-trench drains environments are not always dry and empty. On the contrary, they are sometimes filled with different contents, the most common one being water, as one of the primary objectives of a drain is to collect water runoff from the surrounding buildings and houses and convey it to an outfall. In other scenarios, the open-trench drain’s floor might be filled with liquids, soil, foliage from the surrounding trees, and even, trash.